ENSEÑAR Y APRENDER LA HISTORIA DESDE LA MEMORIA HISTÓRICA - Ángel Felipe Jevey Vázquez; Deinova Leyva Rúa (University of Las Tunas, 2018)
Este artículo incursiona en una importante problemática relacionada con el tratamiento que ha recibido la memoria histórica como elemento esencial para enseñar y aprender la historia del lugar donde vivimos. Tiene como objetivo explicar la importancia de la memoria histórica para la salvaguarda patrimonial de la historia personal, familiar, local y nacional, a partir de su relación con la gestión comunitaria de la escuela, y sobre la base de la contextualización educativa de esta categoría, tan necesaria en las actuales circunstancias ideológicas de la nación cubana. La memoria histórica, desde nuestra visión, es uno de los componentes del patrimonio inmaterial de los pueblos que más requiere ser atendido y aprovechado en nuestras escuelas. Sus potencialidades como categoría cultural requieren ser utilizadas en la tarea educativa de estas. ABSTRACT This article ventures into a major problem related to the treatment he has received historical memory as essential element for teaching and learning the history of the place we live in. The historical memory, in our view, is one of the components of the intangible heritage of the people who most need to be attended to and exploited in our schools. The potential of historical memory as a cultural category needs to be known from science and used in the educational work of the school. These reasons make this article has the purpose to explain the importance of historical memory for heritage safeguarding personal, family, local and national history, from its connection with the management of the school community, and on the basis of educational contextualization of this category, as required under current ideological circumstances of the Cuban nation. KEY WORDS: historical memory, personal memory, family memory, local memory, cultural identity